2022
DOI: 10.1111/nuf.12810
|View full text |Cite
|
Sign up to set email alerts
|

Caring for COVID‐19 infected patients admitted to redesignated coronavirus ICUs: Impact on nurse stress and burnout

Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic globally impacted healthcare due to surges in infected patients and respiratory failure. The pandemic escalated nursing burnout syndrome (NBS) across the workforce, especially in critical care environments, potentially leading to long-term negative impact on nurse retention and patient care. To compare self-reported burnout scores of frontline nurses caring for COVID-19 infected patients with burnout scores captured before the pandemic and in non-COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(179 reference statements)
1
3
0
Order By: Relevance
“…These findings are consistent with those of a study conducted in Oman on various nursing populations 31. Working longer shifts and having a heavier workload owing to a nurse shortage have been linked to job burnout 46,47. In their study, Roney et al47 discovered that increasing levels of burnout were attributable to the increased effort associated with working an extra shift.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are consistent with those of a study conducted in Oman on various nursing populations 31. Working longer shifts and having a heavier workload owing to a nurse shortage have been linked to job burnout 46,47. In their study, Roney et al47 discovered that increasing levels of burnout were attributable to the increased effort associated with working an extra shift.…”
Section: Discussionsupporting
confidence: 81%
“…31 Working longer shifts and having a heavier workload owing to a nurse shortage have been linked to job burnout. 46,47 In their study, Roney et al 47 discovered that increasing levels of burnout were attributable to the increased effort associated with working an extra shift. Similarly, Kumar et al 46 discovered that nurses who worked extra shifts in the previous month were considerably more likely to experience burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of the meta‐analysis were limited due to high heterogeneity, which were possibly caused by the huge variety of interventions, the results consistently indicated that interventions targeting nurses with direct involvement with COVID‐19 patients yielded greater improvements. This could be attributed to the heightened baseline stress with an additional worry of working in a critical care environment such as COVID‐19 ICUs (Roney et al., 2022), although there was evidence disputing this claim (Tamrakar et al., 2021). Another factor could be the substantial increase in workload brought about by the pandemic (Qureshi et al., 2022), resulting in time scarcity for much‐needed reactional activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the U.K., the incidence of nursing burnout in general has been exacerbated by the additional demands that COVID-19 created [ 9 , 10 ]. Already stretched services experienced increased demand upon resources as well as increased staff vacancies across the National Health Service (NHS).…”
Section: Background and Introductionmentioning
confidence: 99%